Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan Departemen Produksi di PT M Otomotif Karawang - Muhamad Sapto Nugroho; Wanta; Dwi Epty Hidayaty (Economic Reviews Journal, 2025)
Intense competition in the automotive industry necessitates companies to maintain product quality and optimize productivity. This study aims to analyze the partial and simultaneous effects of organizational culture job satisfaction on employee work productivity at PT M Otomotif Karawang. A quantitative method was employed, with Path Analysis as the main data analysis technique via SPSS. The population consisted of active employees in PT M Otomotif Karawang's production department, and a representative sample was determined through random sampling. Research instruments proved valid and reliable, and classical assumptions were met. Results show a high level of strength positive relationship between organizational culture with job satisfaction (correlation 0.870, Sig. 0.000). Based on partial hypothesis tests, organizational culture (path coefficient 0.453, Sig. 0.003) significantly influenced work productivity. However, job satisfaction (path coefficient 0.258, Sig. 0.087) had a positive but not significant influence. Simultaneously, organizational culture and job satisfaction significantly influenced work productivity (F-count 43.963, Sig. 0.000), explaining 47.5% of productivity variation, with the remaining 52.5% explained by another variable.